'Endless Wonder' for Whom?: Adaptation, Transformation, and Magical Libraries. (10th March 2020) - Anjirbag, Michelle Anya
Abstract: Books such as Polly Shulman's The Grimm Legacy series, and made-for-television films and television series such as The Librarians and Warehouse 13 incorporate the idea of a library or repository where artefacts connected to various stories are stored that facilitates new adventures, not through retelling, but by using the space of the library as a contact point for people to encounter the artefacts, linking the past and the present. Though not adaptations per se, they challenge ideas of adaptation, transformation, and fidelity, and offer a new way to access different narratives. The library embedded in the book is a focal point for a societal nostalgia for libraries as potential spaces for knowledge and wonder, reflecting the push to protect libraries in contemporary society. The library artefacts become mechanisms for new, wondrous experiences, connected to and informed by knowledge from the past. The mechanism of the fantasy relies on a meta-construction of the library within the story as a portal, insofar as it relies on the recognizability of the stories embedded within the narrative as symbolically constructed 'artefacts'. The library here is not just an archive, but a contact zone for wonder in an increasingly digitized age, and a departure point for a new fantastic journey. These narratives become as much about adapting the library as a concept—recalling, renewing, and renegotiating the potential for wonder, discovery, and egalitarian access to knowledge that they can symbolize—as they are about incorporating old stories into new narratives.